PERANAN BAITUL MAAL WAT TAMWIL DALAM MENINGKATKAN USAHA MIKRO MELALUI PEMBIAYAAN MUDHARABAH (Studi Kasus BMT Fajar Cabang Cileungsi Bogor Periode 2018-2019) - Edy, Sarwo; Rayuningsih (DPPM Universitas Pelita Bangsa, 2021)
This research is motivated by the presence of Islamic Microfinance Institutions in the form of BMT, namely BMT Fajar in the community, especially the people of Cileungsi-Bogor, is expected to bring changes in various aspects of people's lives. In the case of the people of Cileungsi Village, Bogor Regency, where the community is not familiar with Sharia Microfinance Institutions such as BMTs well. Until finally people prefer to make loans to Mobile Banks or so-called loan sharks with interest that are not small as business financing capital, it is the habit of borrowing capital to loan sharks that is the problem and attracts the author's interest to do research. This study aims to determine the background of BMT Fajar in providing mudharabah financing, to know the mudharabah financing procedure, and to determine the role of mudharabah financing in BMT Fajar. The methodology used in this study used a qualitative approach, namely field research and library research. Field research is data collection techniques using observation, interview and documentation methods with Branch Heads, BMT Fajar Cileungsi-Bogor UMKM entrepreneurs, and their business customers. So as to get accurate data on the research process, and library research data, namely by means of data analysis using inductive, deductive and comparative. Through interviews and observations, it can be seen that based on the results of the research it can be concluded that the role of BMT Fajar's Cileungsi branch in improving micro-businesses is by BMT Fajar to provide financing products that are not difficult in terms of capital, which do not apply the usury system in the operational system, but are replaced with a profit sharing system. between BMT and members in accordance with Islamic Sharia. One of them is through Mudharabah financing. Because they saw many Little Pengusa who had gone out of business. Whereas Small and Medium Enterprises have the potential for development in facing the Economic Crisis.